Polymerase Chain Reaction for Prognosis Assessment and Monitoring of the Epstein-Barr Virus-Associated Hodgkin’s Lymphoma - MA Katin; IV Zhil’tsov; VM Semenov; DK Novik (Клиническая онкогематология)
The review provides the analysis of 34 papers on polymerase chain reaction (PCR) as a method of the Epstein-Barr virus (EBV) DNA detection in biological material of patients with EBV-associated cancer diseases including Hodgkin’s lymphoma (HL). A comparative analysis of different methods of EBV DNA detection in biological material is presented. EBV is associated with HL in 20 to 100 % of cases depending on a geographic region and HIV status. EBV-associated HLs are characterized by latency type II. EBV is found in all the atypical cells and can be detected in blood of EBV-associated HL patients by means of the PCR method. The review includes the results of studies on EBV detection using the PCR method compared to in situ methods of hybridization and immunohistochemistry in various EBV-associated cancer diseases including HL. The obtained data indicate that PCR can be used for quantitative determination of EBV DNA in blood plasma of HL patients for therapeutic efficacy monitoring and prognosis assessment of disease and relapses. Quantitative determination of EBV DNA in blood plasma of HL patients using the real time PCR method is a promising technique. Its further practical application requires standardization of the method, larger trials, and comparison to positron emission tomography.